The WAS Project—Waterscape Archaeology in Sicily at Isola delle Femmine (PA, Italy): Submerged and Emerged Heritage - Giovanna Bucci (Heritage, 2022)
The WAS—Waterscape Archaeology in Sicily—project is dedicated to underwater cultural heritage mapping, knowledge and awareness of the cultural heritage, dissemination, and analysis of the submerged environment concerning the coast. The prototype investigation site presented here is Isola delle Femmine (PA, Italy). This paper highlights the archaeological discovery with a description of the main finds, across a multidisciplinary approach, carried out with low-cost technology, increasing sustainable diving, and underlining the relationship between submerged and open-air historical evidence. Our studies address the realization of new underwater archaeological itineraries connected to local history. This text provides a historical-archaeological introduction to understanding the context of the site and, with some geological notes, illustrates the phases of the research with a presentation of the main artifacts, with a focus on the methodology and the techniques of the surveys and the usefulness of underwater photogrammetry and 3D modeling with a particular focus on the tourism application in the diving centers. Our work has allowed for the creation of two new underwater archaeological itineraries of Sicily. The innovative aspects of our project are linked to a new holistic approach in the context of the scientific synergy between multiple disciplines.